Bereavement following a fatal overdose: The experiences of adults in England and Scotland. (2nd January 2017) - Templeton, Lorna; Valentine, Christine; McKell, Jennifer; Ford, Allison; Velleman, Richard; Walter, Tony; Hay, Gordon; Bauld, Linda; Hollywood, Joan
Abstract: Aims : Overdoses contribute disproportionately to drug-related deaths (DRDs) in the UK, yet little is known about the experiences and needs of those who are bereaved by such deaths, and how their experiences and needs might differ from other bereavements associated with substance use. Methods : An interview study with 32 adults in England and Scotland (part of a larger study). Findings: Five themes describe the core experiences of this group of bereaved people: drug use, the death, official processes, stigma, and overdose awareness and prevention. Together, these findings offer new insights in to the key features of this type of bereavement; for example, living with substance use including previous overdoses, difficult circumstances surrounding the death, having to negotiate the complex procedures involved in processing the death, the stigma such deaths attract, and feelings of guilt, self-blame and an unworthiness to grieve. Conclusions : There are ways in which bereavement following an overdose differs from bereavement following other deaths associated with alcohol or drugs. Understanding the experiences and needs of this marginalised group can help improve support for them. Furthermore, this group's experience of witnessing and/or responding to previous overdoses indicates the value in prevention programmes targeting relatives/friends.